Diversity of Fish and Mapping Distribution of Invasive, Banned and Protected Fish at Rawadanau Concervation Area Banten - Eko Hendri Gunawan; Jamadi Jamadi (Jurnal Perikanan dan Kelautan, 2016)
Rawadanau Conservation Area has main function to take care of biodiversity. Theresearch of fish diversity and Invasive Alien Species has been conducted. Theresearch was conducted in August-September 2015. The aim is to show the valueof community structures such as index of fish diversities, the similarities,dominances and alien species. We found nine species contain 198 fish, the detailsare 63 fish at Muara station, 73 fish at Jamungkal and 62 at Cibungur. Thecategory of Biodiversity index showed low category, as follows 1.7306, 1.1146and 1.2153. The category of similarity index showed low-middle category between0.259786 – 0.417703. The details are 0.417703 at Muara Station (middlecategory and labil community); 0.259786 at Jamungkal Station and 0.294471 atCibungur Station (Low Category and depressed community), dominancy index isin low category between 0.268-0.353, it is 0.268 at Muara Station, 0.353 atJamungkal Station and 0.320 at Cibungur Station. The endemic fish are spottedgouramy, common snakehead, climbing gouramy, gondang snail and silver barbfish. Alien species are plecos, pomfret, carp and catfish. The water temperature26-27 oC, pH between 5.76-6.16,water depth 150 s/d >200 m, brightness 53.3-66.6 m, current speed 0.12-0.15 (m/s), DO 6-6.3 mg/l and bog sediment.